The haunted showboat - Keene, Carolyn (New York : Grosset & Dunlap Publishers, 1981)
Nancy Drew and her friends travel to New Orleans for Mardi Gras to solve a mystery surrounding a showboat.
Keywords: Drew, Nancy (Fictitious character) -- Juvenile fiction; River boats -- Juvenile fiction; Carnival -- Juvenile fiction; Haunted places -- Louisiana -- New Orleans -- Juvenile fiction; Drew, Nancy (Fictitious character) -- Fiction; Mardi Gras -- Fiction; Showboats -- Fiction; River boats -- Fiction; Haunted places -- Louisiana -- New Orleans -- Fiction; New Orleans (La.) -- Juvenile fiction; New Orleans (La.) -- Fiction; Detective and mystery fiction; Detective and mystery fiction